PENDIDIKAN KESEHATAN TENTANG ANEMIA PADA REMAJA PUTRI DI SMPN 9 PEKANBARU - Lailiyana, Lailiyana; Susilawati, Elly; Sari, Septi Indah Permata (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2025)
Anemia is a health problem that is often experienced by adolescents, especially young women. This condition occurs when the body lacks hemoglobin in the blood, which functions to carry oxygen throughout the body. Adolescent girls are at a higher risk of developing anemia due to various factors, such as a poor nutritional diet, menstruation, and a lack of understanding of the importance of iron intake. The results of the 2020 Indonesian Demographic and Health Survey (SDKI) found that 29.6% of adolescent girls aged 10-18 years in Riau Province suffered from anemia. The impact of anemia on adolescents includes reduced productivity, especially low academic achievement and other creative activities. The main cause of anemia in adolescent girls is an imbalance in nutritional intake containing iron triggered by a lack of knowledge about foods containing iron. The purpose of this community service activity is to increase adolescent girls' knowledge about anemia. The activity was carried out at SMPN 9 Pekanbaru and was attended by 30 ninth grade female students. The method of the activity was to provide education in the form of counseling in one meeting for approximately 2 hours including brainstorming, games and questions and answers. The material presented was about; the definition of anemia, the causes and impact of anemia on the health of adolescent girls. The activity was evaluated using pretest and posttest questionnaires. The results showed an increase in adolescents' knowledge before and after the education, from an average score of 7.26 in the pretest to an average score of 9.76 in the posttest. Adolescents need to be regularly educated about anemia as a way to prevent anemia in adolescent girls and its impact on health.